Peran Kepuasan Kerja dalam Memediasi Pengaruh Total Quality Management terhadap Kinerja Perusahaan Pada PT. Bali Daksina Wisata - Astini, Ni Komang Tri; Mandala, Kastawan (Universitas Batanghari Jambi, 2024)
Company performance is the overall appearance of the company's work as measured by predetermined standards. These standards can be achieved if the company is able to maintain the quality of the products produced. One way to maintain this quality is by implementing Total Quality Management (TQM). The purpose of implementing TQM is to improve service quality in the hope of meeting and satisfying the needs and expectations of target customers. Customer expectations can be created if there is job satisfaction from employees. Thus, this study aims to examine the effect of implementing TQM elements on Company Performance mediated by Job Satisfaction at PT Bali Daksina Wisata (BDW). This research was conducted at PT.BDW, the sample used was all company employees totalling 60 people with a saturated sampling method (cencus method). Data collection uses a survey approach, with the research instruments used are interviews, questionnaires and observations. The data that has been collected is then processed using path analysis techniques. The analysis results show that TQM is able to influence Company Performance mediated by Job Satisfaction positively and significantly. Based on the results of this study, the company should increase employee job satisfaction again because the resulting effect is quite low.